Role of academia-industry collaboration in enriching engineering education: A case study in sub-sahara context - A, Agarwal; O.M, O.M.; M.T, Letsatsi; R, Marumo; T, Mokgwathi (International Journal of Engineering and Technology, 2018)
Education and training stays one of the key parts of technical institutions, particularly in sub-Sahara nations where the absence of talented laborers is a noteworthy bottleneck impeding the intensity and imaginative limit of firms. Building instruction is deficient with regards to an association amongst information and certifiable issues. Building training as a human undertaking is likewise confronting various extra difficulties of securing, and reception of information, advancement and innovation exchange, fortifying the instructive venture and occupation manifestations. Abilities improvement has been, and still is, an argumentative issue in the scholarly world and in addition mechanical segment. Presently days, the greater part of the universities are confronting the issue of absence of viable learning and experience among their lecturers who have joined the instructing soon after completing their graduation. This paper talks about the necessity of a compelling collaboration amongst the scholarly world and industry which has turned into an undeniably a basic part of productive national development frameworks. Industry encounter enables instructive projects to grow in inventive ways. The contextual investigation examined, demonstrates that such collective endeavors can prompt expanded organization with researchers from various and interdisciplinary foundations.Â Â